Influence of brand on Chinese consumers’ behaviours in Automobile choice: An investigation on Chinese customers’ buying attitudes towards domestic and foreign car brands - Wang, Luqi (2015)
In recent years, branding as a powerful tool to influence consumer behaviors has becoming a hot topic in the marketing literature. But few studies focus on the influence of brands on Chinese consumers’ behaviors, especially their buying attitudes in the automobile market. This dissertation attempts to investigate the influence of brand on Chinese consumers’ behaviors in automobile choice and their buying attitudes towards domestic and foreign brands. The author chose the qualitative research as the most appropriated research approach due to the nature of the topic. The interview was employed to collect the primary data. Ten interviewees attended the interview. And they were selected by using the convenience sampling technique. Finally, the author analyzed the data from the interviews based on the grounded theory. The author generated and analyzed the findings according to accomplish the four objectives of the study. Based on the findings, the author recommended that the Chinese car marketers should do more efforts of enhancing brand awareness and build the brand consciousness. Moreover, the Chinese car makers and marketers should pay more attention to look after and maintain the existing customers. In addition, the Chinese car makers should try their best to change the image in consumers’ minds by improving the quality and changing the brand position. Key words: Brand equity, Symbolic Values, Global brands, local brands, Country-of-origin, consumer ethnocentrism